The potential role of elastography in differentiating between endometrial polyps and submucosal fibroids: a preliminary study - Woźniak, Sławomir (Menopause Review/Przegląd Menopauzalny, 2015)
elastography, ultrasound, endometrial polyps, submucosal fibroids